Hubungan Keterampilan Membaca dengan Hasil Belajar Bahasa Indonesia Siswa Kelas IV UPTD SPF SD Negeri 64 Medde Kabupaten Soppeng (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
Nurmila Auliya. 2023. The Relationship between Reading Skills and Indonesian Language Learning Outcomes for Class IV UPTD SPF SD Negeri 64 Medde, Soppeng Regency. Thesis. Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, University of Muhammadiyah Makassar. Supervisor I Sitti Aida Aziz and Advisor II Syahruddin.This study aims to determine the relationship between reading skills and learning outcomes for Indonesian language students in class IV UPTD SPF SD Negeri 64 Medde, Soppeng Regency. This type of research is a quantitative correlation research. The population of this study were all students of class IV UPTD SPF at SD Negeri 64 Medde, Soppeng Regency. The sample of this research is 19 people. Data analysis techniques were carried out using descriptive analysis techniques and correlation analysis between the independent variables and the dependent variable by utilizing SPSS version 23.The results of this study indicate that the correlation coefficient between reading skills and Indonesian learning outcomes is rxy = 0.947, this correlation is included in the very strong category and sig. shows the number 0.000 which shows that there is a significant difference between reading skills and Indonesian learning outcomes because p < 0.05 (0.000 < 0.05). Thus it can be concluded that there is a significant relationship between reading skills and the results of learning Indonesian for class IV UPTD SPF SD Negeri 64 Medde, Soppeng Regency.